Mitral Valve Transcatheter Edge-to-Edge Repair After TAVR: A Nationwide Analysis - Elkaryoni, Ahmed; Saad, Marwan; Darki, Amir; Abdelkarim, Islam; Has, Phinnara; Hyder, Omar N.; Mamdani, Shafiq T.; Sharaf, Barry L.; Gordon, Paul; Lopez, John J.; Abbott, J. Dawn; Stone, Gregg W. (The American journal of cardiology, 2023)
Patients with persistent severe mitral regurgitation after transcatheter aortic valve replacement (TAVR) may benefit from mitral transcatheter edge-to-edge repair (M-TEER). Using the Nationwide Readmission Database, we identified patients who had M-TEER within 6 months after TAVR and compared their outcomes with patients who had M-TEER without previous recent TAVR during the same calendar year between 2014 and 2020. Because Nationwide Readmission Database data do not cross years, analysis was restricted to the last half of each calendar year. End points included in-hospital mortality and 30-day and 90-day postdischarge rehospitalization rates. In 23,885 M-TEER patients, 396 (1.7%) had a previous recent TAVR. The number of post-TAVR M-TEER procedures increased progressively over time from 16 in 2014 to 92 in 2020. Patients who had M-TEER after a recent TAVR versus those without previous TAVR had similar in-hospital mortality (adjusted odds ratio 0.38, 95% confidence interval [CI] 0.12 to 1.23, p = 0.11), but higher rates of 30-day all-cause hospitalization and heart failure hospitalization (adjusted odds ratios 1.34, 95% CI 1.11 to 1.79, p = 0.04 and 1.63, 95% CI 1.13 to 2.36, p = 0.009, respectively). Nonetheless, in patients who underwent M-TEER post-TAVR, the cumulative 90-day all-cause hospitalization and heart failure hospitalization rates were less after M-TEER compared with before M-TEER (from 45.7% to 31.5%, p = 0.007, and from 29.0% to 16.6%, respectively, both p = 0.005). In conclusion, M-TEER procedures after TAVR in the United States are increasing. Patients with M-TEER after TAVR had similar in-hospital mortality as those who underwent M-TEER without recent TAVR, but higher 30-day hospitalization rates. Nonetheless, 90-day hospitalization rates were decreased after M-TEER in patients with previous TAVR.